2012
DOI: 10.1016/j.watres.2012.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Development of surrogate correlation models to predict trace organic contaminant oxidation and microbial inactivation during ozonation

Abstract: a b s t r a c tThe performance of ozonation in wastewater depends on water quality and the ability to form hydroxyl radicals ( OH) to meet disinfection or contaminant transformation objectives. Since there are no on-line methods to assess ozone and OH exposure in wastewater, many agencies are now embracing indicator frameworks and surrogate monitoring for regulatory compliance. Two of the most promising surrogate parameters for ozone-based treatment of secondary and tertiary wastewater effluents are differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
134
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(161 citation statements)
references
References 46 publications
15
134
0
Order By: Relevance
“…The proposed indicator substances for the control and evaluation of ozonation are representative for three groups according to Zimmermann et al (2011) or derived from five groups suggested by Gerrity et al (2012): (1) OMP with high reactivity towards ozone such as carbamazepine or diclofenac (second order reaction constants k O3 above 10 4 M À1 s À1 ), (2) OMP with medium reactivity such as benzotriazole (k O3 ranging from 10 to 10 4 M À1 s À1 ) and (3) OMP with low reactivity (<10 M À1 s À1 ). OMP with low reactivity do not require an organic indicator substance.…”
Section: Ozonationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed indicator substances for the control and evaluation of ozonation are representative for three groups according to Zimmermann et al (2011) or derived from five groups suggested by Gerrity et al (2012): (1) OMP with high reactivity towards ozone such as carbamazepine or diclofenac (second order reaction constants k O3 above 10 4 M À1 s À1 ), (2) OMP with medium reactivity such as benzotriazole (k O3 ranging from 10 to 10 4 M À1 s À1 ) and (3) OMP with low reactivity (<10 M À1 s À1 ). OMP with low reactivity do not require an organic indicator substance.…”
Section: Ozonationmentioning
confidence: 99%
“…UV 254 absorption or fluorescence have been reported for ozonation as well (Bahr et al, 2007;Dickenson et al, 2009;Wert et al, 2009;Nanaboina and Korshin, 2010;Gerrity et al, 2012;Altmann et al, 2014). As UV 254 can be measured on-line, it is the most suitable parameter for process control ).…”
Section: Ozonationmentioning
confidence: 99%
“…The obtained EEM spectra were processed using the fluorescence regional integration (FRI) technique (Chen et al, 2003;Gerrity et al, 2012). Briefly, cumulative fluorescence intensity (/ i ) that quantifies overall response of particular fraction of fluorophores beneath EEM region ''i'' can be determined as HernandezRuiz et al (2012):…”
Section: Fluorescence Spectroscopy Analysismentioning
confidence: 99%
“…Modeling results were obtained using Eq. (6) derived according toGerrity et al (2012). Correlations between the formation of ACA species and relative changes of integrated EEM fluorescence (DIF/IF 0 ) for total fluorophores in wastewater treated using varying ozone doses.…”
mentioning
confidence: 99%
“…The acquisition of 3-dimensional excitation−emission matrices (EEMs) provides a 'map' of contributions of different component classes comprising dissolved organic matter (DOM). This has resulted in the development of fluorescence indexes that have been shown to be useful indicators of water treatment efficacy [15][16][17][18], or surrogate parameters useful for monitoring the fate of EOCs during conventional and advanced wastewater treatments [19][20][21][22][23]. However, to the best of our knowledge, there are no studies dwelling on the use of fluorescence measurements as indicator of treatment performance and EOC surrogate in CW systems.…”
Section: Introductionmentioning
confidence: 99%